Problems facing Local Manufacturers in the Nigerian Agro-Allied Machine Fabrication Industry (2010)
This study investigates the challenges and opportunities of the local industries involved in the fabrication of agrorelated machinery in Nigeria. With the aid of personal interviews, on-spot assessment/visual inspection, a number of problems confronting these local industries were recorded. These include erratic power supply, cost of raw materials, level of automation, noise pollution, occupational hazards, instability in government policies, marketability and a general bias for machines fabricated locally. The government is currently making efforts at reviving the economy, yet the priorities set in addressing the problems of the local economy may not be aligned with the actual priority problems that local companies face in their daily business. The paper makes suggestions on how th e government could better address the primary concerns of the industry in areas like power supply, raw material pro - essing and sensitization of the Nigeria populac, towards appreciating and procuring locally made machines.